PENGARUH LATIHAN SINGGLE LEG SPEED HOP TERHADAP POWER OTOT TUNGKAI SISWA EKSTRAKURIKULER LOMPAT TINGGI SMK NEGERI 5 PEKANBARU (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The problem in this research is the lack of explosive power when jumping and the lack of body flexibility or less bend so that the body is flat when passing the bar only for students taking the extracurricular high jump at SMK Negeri 5 Pekanbaru. The aim of this researchwas to determine the effect of single leg speed hop exercises on the leg muscle strength of extracurricular high jump. The population in this researchwere students who did the long jump extracurricular using a total sampling technique of 13 students. This type of research uses a pre-test-post-test with instruments, namely standing board jumps, data analysis techniques for normality tests and t-tests. Based on the analysis performed, the amount of data from the pre-test and post-test was 221 with a mean value of 17. Then, the 't' test analysis resulted in t_count of 2,098 and t_table of 1,782. Means t_count (2,098) > t_table (1,782) . It can be concluded that there is an effect of single leg speed hop exercise on the leg muscle strength of extracurricular high jump students at SMK Negeri 5 Pekanbaru.Key Words:Singgle Leg Speed Hop Exercise, Muscle Power